Developmental myosins: expression patterns and functional significance - Schiaffino, Stefano (Skelet Muscle, 2015)
Developing skeletal muscles express unique myosin isoforms, including embryonic and neonatal myosin heavy chains, coded by the myosin heavy chain 3 (MYH3) and MYH8 genes, respectively, and myosin light chain 1 embryonic/atrial, encoded by the myosin light chain 4 (MYL4) gene. These myosin isoforms are transiently expressed during embryonic and fetal development and disappear shortly after birth when adult fast and slow myosins become prevalent. However, developmental myosins persist throughout adult stages in specialized muscles, such as the extraocular and jaw-closing muscles, and in the intrafusal fibers of the muscle spindles. These myosins are re-expressed during muscle regeneration and provide a specific marker of regenerating fibers in the pathologic skeletal muscle. Mutations in MYH3 or MYH8 are responsible for distal arthrogryposis syndromes, characterized by congenital joint contractures and orofacial dysmorphisms, supporting the importance of muscle contractile activity and body movements in joint development and in shaping the form of the face during fetal development. The biochemical and biophysical properties of developmental myosins have only partially been defined, and their functional significance is not yet clear. One possibility is that these myosins are specialized in contracting against low loads, and thus, they may be adapted to the prenatal environment, when fetal muscles contract against a very low load compared to postnatal muscles.